Uttalemarkering i tospråklige ordbøker - Selberg, Ole Michael (Nordiske Studier i Leksikografi, 1997)
Using examples drawn mainly from Norwegian, the article discusses ways ofproviding information on stress, tonem, vowel length, vowel quality and mute consonants either by diacritical marking oflemmas and equivalents or in separate brackets.